Enzyme Complex Added to Broiler Diets: Effects on Performance, Metabolizable Energy Content, and Nitrogen and Phosphorus Balance - Pessôa,GBS (2016)
ABSTRACT Two trials were performed to evaluate the effects of an enzyme complex (EC) on broiler performance, metabolizable energy, and phosphorus and nitrogen balance. In the first trial, 960 one-day-old male Cobb broilers were randomly distributed in a 3 x 2 factorial arrangement (three nutritional levels and the inclusion or not of EC), totaling six treatments with eight replicates of 20 birds per pen, and reared until 42 days of age. The control diet was formulated to meet the broilers' nutritional requirements. The other diets contained reduced available phosphorus (P), metabolizable energy, and amino acid levels, considering 100% and 150% of the EC nutritional matrix. The inclusion of the EC (200 g/ton) resulted in better broiler performance, improving weight gain in 4% and feed conversion ratio in 3% (p< 0.05). In the second trial, 240 male broilers were randomly distributed into the same treatments with eight replicates of five birds per cage. The method of total excreta collection was used. There was an interaction (p< 0.05) between diets and EC for P intake, nitrogen (N) intake, and N retention. The EC supplementation improved nitrogen-corrected apparent metabolizable energy values in 2.02% (p< 0.05). Significant effects were observed on phosphorus and nitrogen balance (p< 0.05). Phosphorus retention improved in 10.26%, nitrogen retention increased in 5.3%, while nitrogen excretion decreased in 3.3%. Based on the results of the present study, we recommend the addition of 200 g/t of the enzyme complex to broiler diets, considering nutrient reduction based on 100% of the EC nutritional matrix.